Dual Agents: Fungal Macrocidins and Synthetic Analogues with Herbicidal and Antibiofilm Activities - Laura Treiber; Christine Pezolt; Haoxuan Zeng; Hedda Schrey; Stefan Jungwirth; Aditya Shekhar; Marc Stadler; Ursula Bilitewski; Maike Erb-Brinkmann; Rainer Schobert (MDPI AG, 2021)
Eight analogues of the bioherbicides macrocidin A (1) and Z (2) with structural variance in the size of the macrocycle, its para- or meta-cyclophane character, and its functional groups were synthesized on two modular routes and tested for herbicidal, antibiotic, and antibiofilm activities. Apart from the lead compounds 1 and 2, the structurally simplified dihydromacrocidin Z (3) and normacrocidin Z (4) showed high herbicidal activity in either thistles, dandelions or in both. The derivatives 2, 3, and dibromide 9 also inhibited the growth of Staphylococcus aureus biofilms by ca 70% when applied at subtoxic concentrations as low as ca 20 µM, which are unlikely to induce bacterial resistance. They also led to the dispersion of preformed biofilms of S. aureus, exceeding a similar effect by microporenic acid A, a known biofilm inhibitor. Compounds 3 and 9 showed no noticeable cytotoxicity against human cancer and endothelial cells at concentrations below 50 µM, making them conceivable candidates for application as anti-biofilm agents in a medicinal context.